Functional imaging of cataplexy during status cataplecticus - Chabas, Dorothée; Habert, Marie-Odile; Maksud, Philippe; Tourbah, Ayman; Minz, Michel; Willer, Jean-Claude; Arnulf, Isabelle (Sleep (New York, N.Y.), 2007)
To identify the neural structures and pathways underlying cataplexy during status cataplecticus in a narcoleptic patient, using brain perfusion single photon emission computed tomography (SPECT). A 68-year-old woman with hypocretin-deficient narcolepsy-cataplexy suffered status cataplecticus after having stopped clomipramine. She underwent a 99mTc-ethylcysteinate dimer brain SPECT during an episode of cataplexy; this image was compared with her brain SPECT during an intervening asymptomatic period. Subtraction SPECT coregistered to magnetic resonance imaging (MRI)(SISCOM)-determined anatomic areas differentially perfused during cataplexy and basal wakefulness state. The areas hyperactivated during cataplexy corresponded on brain MRI with the cingular area, the left and right orbitofrontal cortex, the right temporal cortex, and the right putamen. No significant hypoperfused region was observed during the cataplectic episode. Cataplexy during status cataplecticus partially resembles normal rapid eye movement sleep (with high cingular, orbitofrontal, and putamen activity) but without the other imaging characteristics of this state (no hyperactivation of the pons, amygdale, or occipital cortex).